Novel quantitative assessment of myocardial perfusion by harmonic power Doppler imaging during myocardial contrast echocardiography. (18th January 2005) - Yamada, S; Komuro, K; Mikami, T; Kudo, N; Onozuka, H; Goto, K; Fujii, S; Yamamoto, K; Kitabatake, A
Abstract : Objective: To test the hypothesis that the power of the received signal of harmonic power Doppler imaging (HPDI) is proportional to the bubble concentration under conditions of constant applied acoustic pressure, and to determine whether a new quantitative method can overcome the acoustic field inhomogeneity during myocardial contrast echocardiography (MCE) and identify perfusion abnormalities caused by myocardial infarction. Methods: The relation between Levovist concentration and contrast signal intensity (CI) of HPDI was investigated in vitro under conditions of constant acoustic pressure. MCE was performed during continuous infusion of Levovist with intermittent HPDI every sixth cardiac cycle in 11 healthy subjects and 25 patients with previous myocardial infarction. In the apical views myocardial CI (CImyo ) was quantified in five myocardial segments. The CI from the left ventricular blood pool adjacent to the segment was also measured in dB and subtracted from the CImyo (relative CI (RelCI)). Results: CI had a logarithmic correlation and the calculated signal power a strong linear correlation with Levovist concentration in vitro. Thus, a difference in CI of X dB indicates a microbubble concentration ratio of 10 X/10 . In normal control subjects, CImyo differed between the five segments (p < 0.0001), with a lower CImyo in deeper segments. However, RelCI did not differ significantly between segments (p = 0.083). RelCI was lower (p < 0.0001) in the 39 infarct segments (mean (SD) −18.6 (2.8) dB) than in the 55 normal segments (mean (SD) −15.1 (1.6) dB). RelCI differed more than CImyo between groups. Conclusions: The new quantitative method described can overcome the acoustic field inhomogeneity in evaluation of myocardial perfusion during MCE. RelCI represents the ratio of myocardium to blood microbubble concentrations and may correctly reflect myocardial blood volume fraction.